GESKIEDENIS, GELOOF EN DIE EVANGELIES. PERSPEKTIEWE OP DIE VERHOUDING TUSSEN GESKIEDENIS EN TEOLOGIE IN DIE BYBELWETENSKAPPE = HISTORY, FAITH AND THE GOSPELS. PERSPECTIVES ON THE RELATIONSHIP BETWEEN HISTORY AND THEOLOGY IN BIBLICAL STUDIES - De Villiers, Pieter G. R. (Scriptura, 2002)
This article investigates the relationship between history and theology in Biblical Studies by analysing the context in which they should be understood and by referring to the research on the historical Jesus as example of this relationship. The notions of history and of faith are defined, with further discussion of the nature of the Gospels as documents that mediate the history of Jesus. It concludes with remarks on the prehistory and function of the Gospels.